2014
DOI: 10.1002/jcd.21419
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Complete Equipartite Multigraphs into Cycles of Variable Lengths: The Amalgamation‐detachment Approach

Abstract: Abstract:Using the technique of amalgamation-detachment, we show that the complete equipartite multigraph λK n×m can be decomposed into cycles of lengths c 1 m, . . . , c k m (plus a 1-factor if the degree is odd) whenever there exists a decomposition of λmK n into cycles of lengths c 1 , . . . , c k (plus a 1-factor if the degree is odd). In addition, we give sufficient conditions for the existence of some other, related cycle decompositions of the complete equipartite multigraph λK n×m .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…This result was recently generalised to complete multigraphs [6]. Partial results have also been obtained for decompositions of complete bipartite graphs [9,12,19] and complete multipartite graphs [1]. Here, we add to this body of work by addressing the question of when a complete graph with a hole admits a decomposition into cycles of arbitrary specified lengths.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This result was recently generalised to complete multigraphs [6]. Partial results have also been obtained for decompositions of complete bipartite graphs [9,12,19] and complete multipartite graphs [1]. Here, we add to this body of work by addressing the question of when a complete graph with a hole admits a decomposition into cycles of arbitrary specified lengths.…”
Section: Introductionmentioning
confidence: 89%
“…It is routine to check using (v) that some pair in the appropriate row will always satisfy these conditions. Case (a 3 , c 3 ) (1,2) This choice ensures that a 2 , a 3 , c 2 and c 3 are nonnegative integers such that a 2 is even, a 2 + a 3 = a, c 2 + c 3 = c,…”
Section: Lemma 28 Let U ≥ 5 and W ≥ 8 Be Integers Such That U Is Oddmentioning
confidence: 98%
“…A C α 4 , C β 5 -decomposition of K m • K n was given by Fu [22]. Moreover, Bahmanian andŠajna [7] showed that if K m (λn) has a decomposition into cycles of lengths k 1 , k 2 , . .…”
Section: And the Directed Hamilton Cycle Decompositions Of The Symmetmentioning
confidence: 99%
“…In an earlier paper [6], the authors of the present paper developed a technique for constructing a (c1m,,ckm)‐cycle decomposition of λKn×m from a (c1,,ck)‐cycle decomposition of λmKn. This method, detachment, was applied to the decompositions guaranteed by [10], resulting in many new cycle decompositions of complete equipartite multigraphs.…”
Section: Introductionmentioning
confidence: 99%